Fifty Key Works of History and Historiography. - Stunkel, Kenneth R. (Taylor & Francis, 2011)
Fifty Key Works of History and Historiography introduces some of the most important texts ever written by those who have sought to understand, capture, query and interpret the past. The works covered include texts from ancient times to the present day and from different cultural traditions ensuring a wide variety of schools, methods and ideas are introduced.